Effects of three feedback conditions on aerobic swim speeds - Perez Soriano, P.; Llana Belloch, S.; Brizuela Costa, G.; Encarnacion Martinez, A. (Journal of Sports Science & Medicine, 2009)
The purpose of this study was twofold: (a) to develop an underwater chronometer capable to provide feedback while the athlete is swimming, as well as being a control tool for the coach, and (b) to analyse its feedback effect on swim pace control compared with feedback provided by the coach and with no feedback, in 25 m and 50 m swimming pools. 30 male swimmers of national level volunteer to participate. Each swimmer swam 3 x 200 m at aerobic speed (AS) and 3 x 200 m just under the anaerobic threshold speed (AnS), each swam repetition with a different feedback condition: chronometer, coach and without feedback. Results (a) validate the chronometer system developed and (b) show that swimmers pace control is affected by the type of feedback provided, the swim speed elected and the size of the swimming pool.